Comparison of Web 2.0 Use on State University Websites in Indonesia and Top World Universities Related to Webometric Ranking - Handaru Jati (Elinvo (Electronics, Informatics, and Vocational Education), 2022)
The present work determines the presence in the web 2.0 that twenty universities had through their educational portals. The universities are selected according to the Webometrics ranking (the ten best located in Indonesia and the best located worldwide) to identify what Web 2.0 tools they use. This study explores the educational portals of the twenty selected universities to determine which Web 2.0 tools they use and variables of the tools found will be assessed. The  study only considers those Web 2.0 tools which are linked to the websites of universities. Of the two most used tools, the relevant indicators are quantified from Youtube "Subscribers" and "Views " and Twitter "tweets" following", and "followers". Afterward, the results are shown and analyzed to establish possible relationships between the indicators of each tool. The results reflect the heterogeneous and, in many cases, polarized presence that universities had on web 2.0 through their educational portals. We hope that the work will help universities have a verifiable reference instrument to develop their academic communication strategies through these tools on the way to a 2.0 university model.